Spontaneous Loculated Pneumomediastinum in a COVID-19-Infected Patient - Jafari, Sirous; Jahani, Zahra; Alikhani, Reihane; SeyedAlinaghi, SeyedAhmad; Hasannezhad, Malihe; Salahshour, Faeze; Asadollahi-Amin, Ali (Case Reports in Infectious Diseases, 2022)
While we are still learning about COVID-19 affecting people, older persons and persons with underlying diseases such as high blood pressure, heart disease, and diabetes mellitus (DM) appear to develop serious illness and more complications often than others. In this report, we presented a patient with spontaneous pneumomediastinum after COVID-19. The patient was a 61-year-old man with a history of DM, hypertension, and heart failure, who has been infected with COVID-19. The patient was diagnosed with COVID-19 based on RT-PCR analysis of nasopharyngeal samples, and chest X-ray showed patchy infiltration upper and lower lobes bilaterally. By day 4, imaging was repeated, performed due to exacerbation of pleuritic chest pain, decreased O2 saturation (80%), and coughing that revealed multiple ground-glass opacities bilaterally, and interlobular septal thickening with emphysema in most of the left upper lobe and a small part of right upper lobe which led to severe spontaneous left pneumomediastinum and parenchymal consolidation was also observed. The combination of a chest tube, antibiotics (vancomycin 1 gr/bid and meropenem 1 g/bid), and antiviral (hydroxychloroquine 200 mg/bid and atazanavir 300 mg/daily) was prescribed, and continued treatment with antiviral and appropriate care for pneumomediastinum was successful. Spontaneous pneumomediastinum in the context of COVID-19 should be considered as a prognostic factor in favor of worsening diseases.